Laddering : unlocking the potential of consumer behavior - Holzclaw, Eric V. (Hoboken, New Jersey : John Wiley & Son, Inc., 2013)
Laddering explains how to better understand your customers' core values. Learn to ask the right questions from your customers, use it to analyze.
History -- The need for laddering : BellSouth case study: but would you? -- Laddering defined : cruise line case study -- The steps to laddering : the social TV case study -- Confirming and fine-tuning your ladders: The social media family case study -- Latticing: finding the overlap in ladders: travel personas case study -- Lensing -- Practical application of laddering : Bissell word-of-mouth marketing case study -- The way foreword
Includes index.
Keywords: CONSUMER BEHAVIOR